(untitled) - The Japan economic research center (Tokyo, 1972)
This book introduce analysis of the spread of the use of modern inputs within the framework of agricultural production. Effects of the spead of the use of modern inputs upon the agrian structure. Industrialization and economic development under the new agricultural situation.
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects